Identification of marker-trait associations for oil content in safflower (Carthamus tinctorius L.): Identification of marker-trait associations for oil content in safflower (Carthamus tinctorius L.) - B USHA KIRAN; V DINESH KUMAR; A UMA (Journal of Oilseeds Research, 2023)
Increasing seed oil content is one of the most important goals in breeding of Safflower (Carthamus tinctorius L.). In this study, we identified five marker-trait association and candidate gene (CtDGAT1) showing strong association with oil content in safflower.